Pengaruh Aplikasi Pgpr Terhadap Pertumbuhan Dan Produksi Tumpang Sari Tanaman Jagung Manis (Zea Mays Saccharatta Sturt L.) Dan Tanaman Cabai Rawit (Capsicum Frutescens L.) - Saragih, Ermancah; Gusmeizal, Gusmeizal; Rahman, Abdul (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
This study aimed to determine the effect of Plant Growth Promoting Rhizobacteria (PGPR) application on the growth and yield of intercropped sweet corn (Zea mays saccharatta Sturt L.) and chili pepper (Capsicum frutescens L.). The experiment was conducted from June to August 2022 in Percut Sei Tuan, Deli Serdang, North Sumatra, using a Split-Plot Design with two factors: cropping system (sweet corn monoculture, chili monoculture, and intercropping) and PGPR concentration (0%, 1%, 2%, and 3%). Observed parameters included vegetative growth and yield components. The results showed that the cropping system significantly affected plant height and leaf number of sweet corn, and the number of productive branches of chili. PGPR application had no significant effect on sweet corn growth and yield but significantly affected stem diameter and yield per plot of chili. The interaction between intercropping and PGPR significantly affected chili growth but not sweet corn. Therefore, PGPR application was more effective in enhancing chili growth and yield than sweet corn under intercropping systems.